Dynamics of intersexual dominance in a highly dimorphic primate - Smit, Nikolaos; Ngoubangoye, Barthélémy; Charpentier, Marie J. E.; Huchard, Elise (Frontiers in Ecology and Evolution, 2022)
Intersexual dominance, which is measured by the probability that members of one sex elicit submission of members of the other sex during agonistic interactions, is often skewed in favor of males. However, even in sexually dimorphic species, several factors may influence intersexual dominance. Here, we use an 8-year dataset to examine the dynamics of intersexual dominance in wild-living mandrills (Mandrillus sphinx). Mandrills exhibit an extreme male-biased sexual size dimorphism but females show pronounced kin-differentiated social relationships and occasionally form coalitions against males. We established intersexual hierarchies across consecutive 6-month time blocks, representing either mating or birth seasons. Although females appeared to outrank 11% of males, they elicited male submission in only 2% of agonistic interactions against males. This discrepancy is likely due to the temporary residency of most males in the exceptionally large mandrill groups, the sexually coercive male mating strategies and the scarce number of agonistic interactions within most dyads, that may limit hierarchical inferences. In a second step, we found that the intersexual hierarchy mixes the intrasexual ones respecting their respective order. Females outranked mostly young males during the mating (vs birth) season and social integration was positively correlated to dominance status in both sexes. In a third step, we found that females win more conflicts against young or old males which are closer to them in the intersexual hierarchy. These results extend our understanding of female-male dominance relationships by indicating that female mandrills occasionally outrank males who are considerably larger than them, and that a combination of demographic and social factors can influence the intersexual hierarchy.